2005
DOI: 10.1021/ef049789f
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Benzene Methylation with Methane over MCM-41 and Zeolite Catalysts:  Effect of Framework Aluminum, SiO2/Al2O3 Ratio, and Zeolite Pore Structure

Abstract: The effect of framework aluminum, SiO 2 /Al 2 O 3 ratio, and zeolite pore structures on the oxidative methylation of benzene with methane in a high-pressure batch reactor have been studied using a range of MCM-41 samples and zeolites as catalysts. The presence of framework aluminum in MCM-41 has been shown to be important for providing the required Bro ¨nsted acid sites for the reaction. Among the catalysts tested, HZSM-5, CoZSM-5, and H-beta were found to exhibit the best performance, while mordenite was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Several protic and metal exchanged zeolites as well as ordered mesoporous silicates have been tested in the high-pressure oxidative alkylation of benzene and toluene with methane [18][19][20]. Regarding benzene, it has been shown that molecular sieves bearing acidic sites of moderate strength are responsible for the alkylation step, employing the endo-generated methanol as alkylating agent.…”
Section: Oxidative Conversion: Ocm and Methylation Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several protic and metal exchanged zeolites as well as ordered mesoporous silicates have been tested in the high-pressure oxidative alkylation of benzene and toluene with methane [18][19][20]. Regarding benzene, it has been shown that molecular sieves bearing acidic sites of moderate strength are responsible for the alkylation step, employing the endo-generated methanol as alkylating agent.…”
Section: Oxidative Conversion: Ocm and Methylation Processesmentioning
confidence: 99%
“…By contrast, when strong acidity is brought into play, as in the case of H-beta zeolite, an alternative reaction pathway is able to operate by using fragments derived from the cracking of benzene as alkylating agents, and, in this case, the reaction can proceed in the absence of oxygen [17]. The need for a moderate acidity is appraised from the results from Adebajo et al [19,20] in the alkylation of benzene with CH 4 at a pressure of 6.9 MPa and a temperature of 400 • C in a batch reactor. Thus, as shown in Table 21.1, MCM-41 mesoporous silica in its pure silica form or containing Cu do not hold acid sites with the required strength as to catalyze the reaction, while this mesoporous molecular sieve becomes active when it is synthesized as an aluminosilicate, owing to the presence of Brønsted acid sites.…”
Section: Oxidative Conversion: Ocm and Methylation Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that addition of molecular oxygen facilitated activation of methane in the coconversion of methane and propane over Ga/beta zeolite . Moreover, for the reaction of methane and benzene, other researchers proposed that the molecular oxygen had a remarkable enhancement on the formation of methylated aromatic products over various zeolites. …”
Section: Introductionmentioning
confidence: 99%